2003
DOI: 10.1539/joh.45.351
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Upper Extremity Cumulative Trauma Disorder in Different Unorganised Sectors of West Bengal, India

Abstract: Cumulative trauma disorder (CTD) is a term used to describe a class of soft tissue injuries and disorders that are caused, precipitated or aggravated by a number of occupational activities. These disorders are frequently observed among workers who perform hand intensive jobs 1) . Occupational exposures such as highly repetitive hand exertions, vibrations and localized mechanical pressure are considered to be factors contributing to the occurrence of CTD 2) . CTDs develop over time due to repetitive stress appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 8 publications
4
20
0
3
Order By: Relevance
“…This result corroborated the studies of Garg [16], Gangopadhyay, Ray, Das, et al [17] and Gangopadhyay, Das, Das, et al [18]. According to Garg, severe discomfort or pain was due to heavy spinal loading and repetitive movement of body parts over an extended period [16].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This result corroborated the studies of Garg [16], Gangopadhyay, Ray, Das, et al [17] and Gangopadhyay, Das, Das, et al [18]. According to Garg, severe discomfort or pain was due to heavy spinal loading and repetitive movement of body parts over an extended period [16].…”
Section: Discussionsupporting
confidence: 89%
“…According to Garg, severe discomfort or pain was due to heavy spinal loading and repetitive movement of body parts over an extended period [16]. The feeling of discomfort (pain) in different parts of the body among the workers may be due to their prolonged working hours and repetitiveness of the work; which may lead to MSD [17]. Gangopadhyay et al also showed previously that continuous bending posture, led workers to suffer from acute pain and discomfort for a long period of time, which mainly led to severe pain and MSD [18].…”
Section: Discussionmentioning
confidence: 99%
“…Almost all subjects suffered from discomfort in different body parts caused by prolonged working hours, constant awkward postures and repetitiveness of the work. Repetitiveness of the work, prolonged working hours and awkward body postures during work may also lead to MSD [14,15,16]. From the observation of the working conditions of the experimental group, it is evident that female prawn seed collectors work in unfavorable conditions; they have to travel a long distance dragging hand-operated nets forwards and backwards through 0.46-metre-deep sticky mud and salty water.…”
Section: Discussionmentioning
confidence: 99%
“…This may have lead to the development of different kinds of musculoskeletal disorders (MSDs) among them (Gangopadhyay et al . )(1) (Ijadunola et al . )(2) observed that poorly designed workstation promote unnecessary physical efforts, which reduce efficiency and productivity also.…”
Section: Introductionmentioning
confidence: 99%